Non-destructive latent fingerprint development and background elimination by Mueller Polarimetry - Chironi, Emanuel (2023)
In this article we have explored the use of Mueller polarimetry for the simultaneous and non-destructive latentfingerprint development and background elimination. This proposal not only expands previously reported uses ofthe polarization state of light for fingerprint development, but offers some advantages. Samples of a few donors,taken on different heavily back grounded substrates, were measured and processed. Several strategies forbackground removal were applied. The results are very promising, since the background was successfully erasedin all cases and the quality of the developed fingerprints was excellent for most substrates and donors.Considering that the method is non-destructive and that the proposed measurement instrument is inexpensiveand portable the method could be tried in real cases with no risk for the evidence. In addition, the success of theprocedure for background removal raises the possibility of exploring if it would work for the enhancement offingerprints developed with other methods.